Soil fertility in agricultural production units of tropical areas - S. Rodelo-Torrente; A.C. Torregroza-Espinosa; M. Moreno Pallares; D. Pinto Osorio; A. Corrales Paternina; A. Echeverría-González (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Soil is the most important basic natural resource for the support of agricultural production systems. Productivity maintenance in these ecosystems depends on their physicochemical. However, there are no significant studies on the current status of soil fertility and quality in tropical areas vulnerable to climate change and lacking management practices. The purpose of this study was to assess the physical and chemical properties of the soil to propose guidelines on soil handling and management in tropical areas.METHODS: Data on texture, macronutrients, micronutrients, and cation ratios were collected at 200 farms in the Sucre Department of Northern Colombia. Correlation analysis and principal component analysis were performed on the resulting data set, and a soil quality index was calculated.FINDING: Macronutrients N, P, K, S, Ca, Mg, and Na displayed average values of 21.65 ± 10.65 part per million, 40.35 ± 67.21 part per million, 0.46 ± 0.43 meq/100g, 7.94 ± 28.35 part per million, 15.63 ± 17.30 meq/100 g, 5.63 ± 3.58 meq/100g, 0.19 ± 0.20 meq/100g, respectively. Micronutrients Cu, Fe, Zn, and Mn displayed average values of 2.20 ± 1.66 part per million, 48.05 ± 37.87 part per million, 1.16 ± 1.26 part per million, 14.22 ± 12.24 part per million, respectively. The predominant texture among assessed soils was sandy clay loam. A significant correlation was found between (Ca/Mg) K-Ca/K, (Ca/Mg) K-Mg/K, Fe-Cu, and Ca-cation exchange capacity. The soil quality index of the soils assessed in the Department of Sucre indicates a high level of quality, which is strongly influenced by the indicators S, P, Mn (≥ 0.90) Fe, Zn, Cu, K, Na (≥ 0.80).CONCLUSION: The macronutrients displayed a deficiency of potassium. It is therefore recommended to monitor these soils and apply fertilization plans according to the needs of each assessed soil. Lastly, this study provides relevant information for proposing guidelines for crop improvement.